COLLABORATIVE GOVERNANCE INADDRESSING VIOLENCE AGAINST WOMEN: A CASE STUDY OF THE PALU WOMEN'S LIBU (Jurnal Studi Inovasi Pemerintahan, 2025)
ABSTRACTViolence against women is a significant human rights violation in Indonesia, fueled by gender inequality. The high number of cases in Palu City (89 cases in 2024) emphasizes the urgency of collaborative management. This study aims toanalyze the implementation of Collaborative Governance (CG) carried out byLibu Perempuan (Independent Legal Aid Institute for Women) in addressingviolence in Palu City. Using descriptive qualitative methods, data were collectedthrough in-depth interviews, observations, and documentation studies withinformants from Libu Perempuan and DP3A. The analysis focuses on fouraspects of CG, as outlined by Ansell and Gash (2008). The results show that CG is driven by an initial condition of a shared need to overcome obstacles to cases. Libu Perempuan takes a leadership role as a facilitator of integrated referralservices. CG's institutional design emphasizes strengthening coordination, enforcing regional regulations (Perda), and a referral system that discouragesmediation of sexual violence. The collaborative process demonstrates responsive
Keywords: Array